Chronic non bacterial osteitis- a multicentre study - Chandrika S. Bhat; Catriona Anderson; Aoibhinn Harbinson; Liza J. McCann; Marion Roderick; Adam Finn; Joyce E. Davidson; Athimalaipet V. Ramanan (BMC, 2018)
Abstract Objective To understand the demographics, clinical features and treatment outcomes of Chronic Non-bacterial Osteitis (CNO) from three tertiary paediatric rheumatology services in the United Kingdom. Methods Children less than 18 years of age diagnosed with CNO between 2001 to 2016 from one tertiary service and between 2001 to 2017 from two tertiary services were included. Clinical notes were reviewed and all pertinent data were collected on a pre-defined proforma. One hundred and thirty one patients were included in the study. The Bristol diagnostic criteria were applied retrospectively. Results Retrospective analysis of the data showed that the disease was more common in girls than boys (2.5:1), median age at onset of symptoms was 9.5 years (IQR 8 to 11 years). Bone pain was the predominant symptom in 118/129 (91.4%) followed by swelling in 50/102 (49.01%). Raised inflammatory markers were present in 39.68% of the patients. Whole body Magnetic Resonance Imaging (MRI) was a useful diagnostic tool. Metaphyses of long bones were most often involved and the distal tibial metaphyses 65/131 (49.6%) was the most common site. Non-steroidal anti-inflammatory drugs were used as first line (81.67%) followed by bisphosphonates (61.79%). Treatment was escalated to a TNF blocker when response to bisphosphonates was suboptimal. The disease was in remission in 82.4% of the patients during the last follow up. Conclusion Our multicentre study describes features and outcomes of CNO in a large number of patients in the United Kingdom. Significance and innovation Raised inflammatory markers were present in 39.68% of our patients.Whole body MRI is useful for diagnosis and also determining response to treatment.A greater number of lesions were detected on radiological imaging compared to clinical assessment.Metaphyses of long bones were most often involved and the distal tibial metaphyses (49.6%) were the most common site.Non-steroidal anti-inflammatory drugs were used as first line (81.67%) followed by bisphosphonates (61.79%).There was no difference in number of medications used for management in unifocal versus multifocal disease.TNF blockers were used with good effect in our cohort.